2019
DOI: 10.1055/a-0942-7479
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Walking Training with Restricted Blood Flow on HR and HRV Kinetics and HRV Recovery

Abstract: The aim of this study was to investigate the effects of walking training with and without blood flow restriction (BFR) on heart rate (HR) and heart rate variability (HRV) kinetics and HRV recovery. Twenty-one men (53.5±3.2 years; 82.4±13.5 kg; 168.5±7.2 cm) were randomly assigned to two training groups: walk training group with (BFR-W; n=11) and without (NOR-W; n=10) BFR. Before and after training, all subjects underwent body composition evaluation, incremental test, and one constant load test. Walking trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 32 publications
1
24
1
Order By: Relevance
“…More recently, Kambič et al (2019) observed a reduced systolic BP of patients with coronary artery disease following 8 weeks of knee extension BFR training (30-40% 1RM; 3 sets of 8-12 reps; 2x/week; BFRP ∼140 mmHg). Lastly, two studies verified an increase in HR variability (Ferreira Junior et al, 2019;Junior et al, 2019). Although literature is inconsistent, there is evidence to support that BFR training may reduce both HR and BP and increase HR variability in clinical populations.…”
Section: Arterial Compliance Stiffness and Diametermentioning
confidence: 89%
See 4 more Smart Citations
“…More recently, Kambič et al (2019) observed a reduced systolic BP of patients with coronary artery disease following 8 weeks of knee extension BFR training (30-40% 1RM; 3 sets of 8-12 reps; 2x/week; BFRP ∼140 mmHg). Lastly, two studies verified an increase in HR variability (Ferreira Junior et al, 2019;Junior et al, 2019). Although literature is inconsistent, there is evidence to support that BFR training may reduce both HR and BP and increase HR variability in clinical populations.…”
Section: Arterial Compliance Stiffness and Diametermentioning
confidence: 89%
“…In young adults, no significant changes were observed in HR and BP following 3 weeks of leg press, knee flexion and knee extension training with BFR (20% 1RM; 2 sets of 10 reps; 3x/weeks; BFRP 20% above systolic BP) (Kim et al, 2009). In contrast, Junior et al showed a reduction in HR of healthy males following 6 weeks of BFR walking training (6 km•h −1 , 5% grade; 5 sets of 3 min; 3x/week; BFRP between 80 and 100 mmHg) (Junior et al, 2019). Similarly, reduced mean BP was observed in healthy young individuals following 4 weeks of BFR handgrip training (30 contractions per minute at 30% MVC; 3x/week; BFRP between 75 and 150% of systolic blood pressure) (Crisafulli et al, 2018) (Kacin and Strazar, 2011).…”
Section: Arterial Compliance Stiffness and Diametermentioning
confidence: 98%
See 3 more Smart Citations